PENGATURAN MODEL PERAMPASAN ASET TANPA PEMIDANAAN UNTUK TINDAK PIDANA KORUPSI YANG MERUGIKAN KEUANGAN NEGARA - Nefa Claudia Meliala (Veritas et Justitia, 2026)
The recovery of assets derived from corruption remains a significant challenge within Indonesia's criminal justice system, particularly where conventional confiscation mechanisms depend upon a prior criminal conviction. This limitation often hinders efforts to restore state financial losses arising from corruption offences. Against this background, this article examines the urgency of adopting a Non-Conviction Based Asset Forfeiture (NCB Asset Forfeiture) regime as an alternative mechanism for asset recovery in corruption cases. This research employs normative legal research methods based on qualitative analysis of secondary data consisting of primary legal materials, including legislation, ratified international conventions, and draft legislation, as well as secondary legal materials such as books, journal articles, and other scholarly works. The research is further supported by empirical findings contained in the Corruption Trend Monitoring Reports published by Indonesia Corruption Watch from 2018 to 2024. The study finds that the existing conviction-based asset forfeiture model under Indonesian positive criminal law is inadequate to address the complexities of corruption and the recovery of illicit assets. Consequently, the regulation of NCB Asset Forfeiture has become increasingly urgent to strengthen asset recovery mechanisms and improve the restoration of state financial losses caused by corruption offences.